Aplikasi Pemasaran Berbasis Web PT XYZ - Hendarti, Henny; Mariani, Vini (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Marketing plays an important role in determining the success of a company's sales. Marketing of goods or services over the Internet opens an opportunity for a company to expand the business into new markets, and compete with other businesses in the same field. It is because the internet offers wider selection of good products, service products, and prices. Thus, customers can be sure in choosing and buying of goods and services. For that e-marketing is introduced as an marketing strategy that integrates internet and marketing. A study was conducted to develop e-marketing application for PT XYZ as a company that produces and sells men’s apparel and accessories. The methodology used in developing the e-marketing application is library research, field research, and a seven-stage approach to build e-marketing. The e-marketing strategy developed is expected to expand market share and increase sales. Additionally, it is expected to be a powerful strategy to build relationships with customers, providing information of both company and its products.